Exploring the Mathematical Conceptual Understanding of Students Using AI Chatbots in Pythagorean Theorem Material - Nur Rahman Nida; Rohati Rohati; Ade Kumalasari (Pendidikan Matematika STKIP Kusuma Negara, 2026)
The rapid development of artificial intelligence (AI) in education has created new opportunities to enhance students’ mathematical conceptual understanding and support more personalized learning experiences. This study aims to explore students’ mathematical conceptual understanding when using AI chatbots in learning the Pythagorean Theorem. This study employs a descriptive qualitative approach, involving eighth-grade junior high school students selected through purposive sampling based on their level of conceptual understanding. Data were collected through a perspective questionnaire, an essay-based test, and semi-structured interviews, and analyzed using data reduction, data presentation, and conclusion drawing. The findings reveal that students were able to meet all indicators of mathematical conceptual understanding, with AI helping them understand definitions, visualize geometric relationships, obtain immediate feedback, and recognize real-world applications of the Pythagorean Theorem. However, students still face difficulties in meeting some of the indicators of mathematical conceptual understanding in the Pythagorean theorem, which were influenced by a tendency to rush and the suboptimal use of AI features. In conclusion, although AI can effectively support conceptual understanding, its integration in learning should be accompanied by teacher guidance to foster metacognitive awareness and deeper, more reflective learning.